Effect of Internal Control Environment System on Financial Performance of Selected Federal Institutions in Oyo State, Nigeria - Oyeniyi Oluwafunmilayo Caroline (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study focuses on the effect of organizational structure and human resource polies nda procedure on financial performance of some selected federal institutions in Oyo State. The methodology of the study is based on survey research approach. The statistical data used for the study were obtained by distribution of one hundred and fifty (150) questionnaire among selected employees, in the five (5) federal institutions considered in this research work. These respondent were selected using non-probability sampling method, the data obtained from the questionnaire were analyzed using multiple regression statistical tools in SPSS (Statistical packages for social sciences.). The result of the analysis shows that organizational structure and human resource polies and procedure has significant relationship with accountability and cost management in the institutions, and this was because the P- value obtained (i.e.0.002) using multiple regression was greater than the benchmark value of 5% specified in SPSS for this analysis. Based on this result, the study recommends that management should develop more effective strategies on organization structure and human resource policy and procedure that will ensure effective and efficient, accountability and cost management